Impact of tree species replacement on carbon stocks in a Mediterranean mountain area, NE Portugal - Fonseca, Felícia (2019)
Forest species replacement can influence significantly the amount of carbon stored in the several compartments that compose the terrestrial ecosystems (biomass, forest floor and mineral soil). This study intends to evaluate the influence of the replacement of the Quercus pyrenaica species (QP), which represents the climax vegetation of Serra da Nogueira, NE Portugal, by the Pseudotsuga menziesii (PM) and Pinus nigra (PN) plantations (fast-growing species). For this purpose, three plots of 314m2 were established in each stand (9 plots in total) and the height and diameter at the breast height of all trees were measured, in order to characterize the stands and estimate the tree biomass. Herbaceous vegetation and forest floor were collected in areas of 0.49m2 in 15 points under each tree species (5 per plot). At the same points, disturbed and undisturbed soil samples were collected at depths 0–5, 5–10, 10–15, 15–20 and 20–30 cm. Thirty years after the climax vegetation replacement, carbon gains are observed in forest species biomass and forest floor (1.3 Mg C ha−1 year−1 in PN and 4.0 Mg C ha−1 year−1 in PM) and significant losses were recorded on soil carbon pool (about 2.2 Mg C ha−1 year−1). Total carbon accumulated is significantly higher in PM (331 Mg C ha−1) compared to PN (246 Mg ha−1) and QP (273 Mg C ha−1), which present statistically similar values. Tree biomass and mineral soil constitute the major carbon pools.